The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/f12111557
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and Biomass Production in Miombo Forest in Huambo (Angola): A Balance between Local and Global Needs

Abstract: Miombo is one of the most widely distributed ecosystems in Angola, with a great social and environmental value. Thus, the rural population uses the biomass as fuel and miombo provides important ecosystem services, such as its carbon sequestration capacity. The objectives of this work were (i) to assess deforestation in miombo forest in Huambo province (Angola) during the last 20 years, (ii) to evaluate carbon storage capacity of miombo, and (iii) to calculate the charcoal productive capacity of those forests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The effects of charcoal production can never be overemphasized, behind the benefits, there have been also negative effects on the environment and human health [23]. A major concern is that this exploration could negatively impact forest regeneration once the annual rate of growth of these forests is low [24,25], as most of the trees in Miombo and Mopane woodlands are slow-growing. The net primary production in Miombo woodlands is estimated to be 900-1600 g m −2 yr −1 and the annual increment of the woody-plant biomass is no more than 3-4% in mature stands [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of charcoal production can never be overemphasized, behind the benefits, there have been also negative effects on the environment and human health [23]. A major concern is that this exploration could negatively impact forest regeneration once the annual rate of growth of these forests is low [24,25], as most of the trees in Miombo and Mopane woodlands are slow-growing. The net primary production in Miombo woodlands is estimated to be 900-1600 g m −2 yr −1 and the annual increment of the woody-plant biomass is no more than 3-4% in mature stands [3].…”
Section: Introductionmentioning
confidence: 99%
“…The net primary production in Miombo woodlands is estimated to be 900-1600 g m −2 yr −1 and the annual increment of the woody-plant biomass is no more than 3-4% in mature stands [3]. Some authors showed that it could take 19 to 55 years to recover the structure after logging [24][25][26][27]. Also, the exposure to wood smoke has been treated as a public health concern meanly the carbon monoxide and the mixture of solid and liquid particles suspended in the air for a long time [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Erythrophleum species have high-quality wood that is hard, dense, heavy and tough and contains a variety of secondary metabolites (e.g. alkaloids, terpenoids and flavonoids) in different parts (leaf, bark, stem or seed), which are valuable for the treatment of many illnesses [ 1 , 4 – 7 ]. Therefore, Erythrophleum species are threatened due to their hardwood and/or biomedical properties in different distribution areas [ 2 – 4 , 6 , 7 ].…”
Section: Objectivementioning
confidence: 99%
“…alkaloids, terpenoids and flavonoids) in different parts (leaf, bark, stem or seed), which are valuable for the treatment of many illnesses [ 1 , 4 – 7 ]. Therefore, Erythrophleum species are threatened due to their hardwood and/or biomedical properties in different distribution areas [ 2 – 4 , 6 , 7 ]. In addition to timber and medicinal uses, Erythrophleum species can be used as ornamental and agroforestry trees [ 8 , 9 ].…”
Section: Objectivementioning
confidence: 99%
“…Charcoal production causes a sizeable environmental impact, like deforestation and forest degradation, and continuously grows in African rural communities (Miapia et al 2021). Then, more knowledge is needed on the chemical properties of miombo wood species, emphasizing those less used for the wood industry and exploited for charcoal and rewood production (Lhate et al 2010).…”
Section: Introductionmentioning
confidence: 99%